Assessment of patient knowledge of cardiac rehabilitation: Brazil vs Canada Avaliação do conhecimento de pacientes de reabilitação cardíaca: Brasil versus Canadá - Ghisi G.L.M. (2013)
Background: Much of the relationship between health status and knowledge about health and disease can be attributed to the combined effects of disparate health-related behavior, environmental conditions, and socioeconomic structures as well as contact with and delivery of health care.Objective: The aim of this study was to describe and compare knowledge of patients with coronary artery disease (CAD) enrolled in cardiac rehabilitation (CR) programs in Brazil and Canada about CAD-related factors.Methods: Two samples of 300 Brazilian and 300 Canadian patients enrolled in CR were compared cross-sectionally. Brazilian patients were recruited from 2 CR centers in Southern Brazil, whereas Canadian patients were recruited from 1 CR center in Ontario. Knowledge was assessed using the Coronary Artery Disease Education Questionnaire (CADE-Q), psychometrically validated in Portuguese and English. The data were processed through descriptive statistics, post-hoc and the Student's t-tests.Results: The mean total knowledge score for the whole sample was 41.42 ± 9.3. Canadian respondents had significantly greater mean total knowledge scores than Brazilian respondents. The most highly knowledgeably domain in both samples was physical exercise. In 13 of 19 questions, Canadian respondents reported significantly greater knowledge scores than Brazilian respondents.Conclusions: Canadian outpatients reported significantly greater knowledge than their Brazilian counterparts. The results also suggest that having a structured educational curriculum in CR programs may contribute to increased patient knowledge, which may ultimately facilitate behavioral changes.